Hubungan Kekuatan Otot Tungkai Bawah terhadap Stabilitas Fungsional pada Pelari Rekreasional - Ni Komang Tri Utami Wulandari; I Putu Gde Surya Adhitya; Indah Pramita; I Putu Yudi Pramana Putra (Universitas Pahlawan Tuanku Tambusai, 2026)
Running is a popular physical activity that provides various health benefits. Running requires good functional stability to maintain dynamic balance during movement. One of the factors that contributes to functional stability is lower limb muscle strength. Decreased lower limb muscle strength may affect postural control and increase the risk of stability impairment. This study aimed to determine the relationship between lower limb muscle strength and functional stability among recreational runners in Denpasar City. This study used a *cross-sectional* design. The sampling technique used was *purposive sampling* involving 46 recreational runners aged 18–30 years. Lower limb muscle strength was measured using a *leg dynamometer*, while functional stability was assessed using the *Modified Star Excursion Balance Test* (mSEBT). Data analysis was conducted using the Pearson correlation test. The results showed a significant relationship between lower limb muscle strength and functional stability with a p-value of 0.007 and a correlation coefficient of r = 0.391, indicating a positive correlation. It can be concluded that increased lower limb muscle strength is associated with improved functional stability. Recreational runners are advised to perform lower limb strengthening exercises regularly.